Republic of Indonesia : Accounting and Auditing - World Bank (Washington, DC, 2012)
The Government of Moldova's Economic Growth and Poverty Reduction Strategy Paper (EGPRSP) lays out an ambitious plan for sustaining growth and poverty reduction and reshaping the government to meet the needs of a market economy. The public expenditures envisaged under this ambitious plan, however, vastly exceed the domestic resources available to the Government. Additional foreign budgetary support may help alleviate some of that resource constraint. Recognizing that the share of tax revenues and expenditures to GDP in Moldova already greatly exceed comparable international levels, generating additional domestic tax resources risks crowding out the private sector and undermining growth prospects. This suggests that in order to finance higher order public expenditures priorities, the Government needs to create fiscal space from within the existing resource envelope. This will require inter and intra-sectoral reallocation of expenditures and an increase in the efficiency of public spending rather than increasing the relative size of government.